Simulation of Performance and Emissions of a Small Scale Gas Turbine Fueled by Syngas - Sadig, Hussain (2013)
Gas turbines are fueled mainly with natural gas and oil. To run gas turbines with new fuels (such as syngas), it is important to study the combustion and performance characteristics for these fuels. This work presents a simulation of performance and emission for small-scale gas-turbine system using ASPEN Plus simulator. The simulation was tested using Liquefied Petroleum Gas (LPG) and two different types of syngas fuels. The effect of fuel composition and heating value on the turbine inlet temperature, output power, and emissions was studied. For the same operation conditions, switching to syngas fuels showed a tendency to reduce NOx emission compared to LPG. On the other hand, CO2 emissions per unit of energy for syngas fuels were doubled. For a heat input range of (50-100kW), the output power for syngas was less by 0.28-4.49% compared to LPG. The gas temperature for syngas combustion showed a different behavior based on the constituent’s presence in each fuel.